Artificial intelligence adoption and workplace training - Mühlemann, Samuel [Verfasser] (My University, 2025)
„As artificial intelligence (AI) reshapes business processes, firms must adapt their training strategies to cultivate a skilled workforce. Using German establishment-level panel data from 2019 to 2023, this study analyzes how firms adjust their training strategies following AI adoption. Staggered difference-in-differences analysis shows that sustained AI adoption is associated with a 14% increase in new apprenticeships among training firms (intensive margin), but is not linked to the training decision (extensive margin). AI adoption is also associated with a modest increase in continuing training, with resources shifting toward high-skilled employees. The results align with AI as an automation innovation that reduces demand for simple skills as well as an augmentation innovation that increases demand for more advanced skills. The German dual apprenticeship system appears critical for firms aiming to build a future-ready workforce in the age of AI.“ (author’s abstract; BIBB-Doku)

„Deutsche Ausbildungsbetriebe, die KI einführen, bauen die Zahl der Ausbildungsplätze für Lernende aus und nicht ab, wie oft befürchtet wird. Dies ist das Hauptergebnis einer Studie von Samuel Mühlemann von der Ludwig-Maximilians-Universität München. Basis der Untersuchung ist das BIBB-Qualifizierungspanel – ein einzigartiger repräsentativer Datensatz mit Informationen zum KI-Einsatz und der Aus- und Weiterbildung. So habe Nobelpreisträger Joel Mokyr bereits für die industrielle Revolution in England die Wichtigkeit von Lehrlingen, die die neue Technologie schnell verbreiteten, belegen können. Zudem fand Mühlemann, dass Betriebe nach der Einführung von KI ihre Mitarbeitenden vermehrt motivieren, sich für hochqualifizierte Tätigkeiten weiterzubilden. Kündigungen und Neueinstellungen von Fachkräften veränderten sich jedoch nicht signifikant, zumindest nicht im Beobachtungszeitraum 2019-2023.“ (BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; G 2.2.1 Technologisierung; 370; Ausbildungsbetrieb; Ausbildungsverhalten; Einflussfaktor; Künstliche Intelligenz; Bildungstechnologie; Medieneinsatz; Auszubildender; Weiterbildungsmotivation; BIBB-Qualifizierungspanel